Portal educativo: saúde de puérperas e recém-nascidos - Silva, Marcela Rosa da (Universidade do Vale do Rio dos Sinos, 2020)
Puerperium is defined as the period starting right after childbirth and finishing when the female body returns to a non-pregnancy state. Although puerperium is a risky period, it is often neglected. Attention is drawn to newborn care, and the changes occurring in this period stay unattended. The aim of this research was to design and validate an educative portal directed to the health of women and newborns. This methodological study was carried out in three stages: netnographic qualitative research; design of the educative portal; and validation of the portal. Thirty-six women with different ages and number of pregnancies participated in this netnographic study. Software MaxQda 2018 was used in the analysis of the results, from which three categories emerged: care and health problems in puerperium; learning to live after giving birth; and newborn care. The first category represents the challenges faced by women in this period of their lives and addresses practical daily problems occurring along the puerperium. The second category points out the subjectivity of this period experienced by women, in association with emotional and psychological problems of this phase. The third category involves the challenges that mothers face on returning home with a new family member who totally depends on them to survive. The results of the netnographic research contributed to the definition of the subjects addressed by the educative portal: breastfeeding, real motherhood, and newborn care. The design of the portal comprised the following steps: a) analysis of needs; b) identification of users; c) organization of contents; d) construction; e) validation; f) maintenance. The portal was validated with a 100% agreement percentage, a content validation index of 1.0 and evaluation of the Lighthouse program with 66.75 points. Thus, the products generated by the study were the construction of Mama Materna Educative Portal and the creation of MamaMaterna brand mark, which is in process of registration.
Keywords: Período pós parto; Enfermagem; Tecnologia; Puerperium; Nursing; Technology; ACCNPQ::Ciências da Saúde::Enfermagem